Anti-Apoptotic Activity of Anthocyanins has Potential to inhibit Caspase-3 Signaling - Sari, Dewi Ratih Tirto; Safitri, Anna; Cairns, James Robert Ketudat; Fatchiyah, Fatchiyah (Journal of Tropical Life Science, 2020)
Caspase-3 is a biochemical marker for cell apoptosis. Several studies focused on exploring caspase inhibitor potential in natural compounds. Hence, in this study investigated the anthocyanins as anti-apoptotic potential activity through caspase-3 using molecular docking. Six types of anthocyanin were retrieved from PubChem database and caspase-3 protein was downloaded from Protein Data Bank. Anthocyanins and caspase-3 protein were docked using HEX 8.0 program and visualized using Discovery Studio 4.1 software. The interaction among cyanidin-3-O-glucoside, delphinidin-3-O-glucoside, pelargonidin-3-O-glucoside, peonidin-3-O-glucoside and petunidin-3-O-glucoside showed similar binding pattern on caspase-3 protein. All of them bind to BIR2 region and allosteric site of caspase-3, which are a crucial site for apoptosis regulation. Interestingly, malvidin-3-O-glucoside also interacted with caspase-3 in BIR1, BIR2 and BIR3 regions. In addition, anthocyanins-caspase-3 complex showed low energy and demonstrated several hydrogen bonds, hydrophobic interactions and van der Waals interactions, which indicated stable interaction. This study implies that all anthocyanins have potential as inhibitor of caspase-3 protein and might have potential as anti-apoptosis. Further in-vitro and in-vivo studies are need to confirm this experimental.